A perception assessment on security awareness in Malaysian government agencies by Rasch model / Mohd Ismail Ahmad, Azrilah Abdul Aziz and Mohd Saidfudin Masodi - Ahmad, Mohd Ismail; Abdul Aziz, Azrilah; Masodi, Mohd Saidfudin (Centre for Media and Information Warfare Studies, 2008)
The Chief Government Security Office (CGSO) in the Prime Minister's Department is responsible for protecting the country against potential threats to the national security. A number of other security and intelligence agencies work alongside CGSO to gather, analyse and utilise information on intelligence and national security matters. In order to protect national security and economic well-being, the CGSO collects and disseminates intelligence, investigates and assesses threats and works with others to counter them. They render advise on protective security and provide effective support of such tasks since 1957 as empowered in Arahan Keselamatan, (Pin.J984). The CGSO also provides protective security advice to multi-national corporations where it involves National Infrastructure Key Points (NIKeP), helping them reduce their vulnerability to possible threats. Ever since the CGSO has established highly competent quality service in discharging their statutory junctions. However, the vital role of the CGSO in the government service has since diminished despite the rise of global terrorism. Subsequently, the CGSO has taken a concerted effort by vigorously carrying out workshops and seminars at various Government Agencies to improve the awareness and put security as being of utmost importance. It is aimed as preventive measures to frustrate sabotage, espionage, prevent damage to the country from subversion and other covert activity; frustrate proliferation of detrimental information, watch out for new or re-emerging types of threat; protect the Government's sensitive information and assets. This paper assessed feedback from Government Officers as participants in workshops and seminars conducted by the CGSO on protective security. The evaluation shows there is a strong correlation between the number of courses conducted and level of security appreciation; hence, higher level of competency in taking protective security measures amongst the government officers.